1988
DOI: 10.1002/aic.690341207
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐transfer effects of bubble streams rising near vertical electrodes

Abstract: Mass-transfer enhancement by a stream of bubbles rising near a planar, vertical surface is resolved spatially and temporally using a micromosaic electrode. A stream of gas bubbles is generated electrolytically, either at a segment directly below and in the plane of the monitoring electrodes, or at a wire tip that can be positioned inside or outside the mass-transfer boundary layer. The mass-transfer enhancement resulting from bubbles rising within the mass-transfer boundary layer is found to be strong and loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…Whitney and Tobias [143] used the MME to study the effect of single columns of electrolytically-generated gas bubbles on the mass transport to a vertically-oriented electrode. They found that a distinction could be made between bubbles generated on the MME itself, at a satellite segment, and bubbles evolved from a wire a some distance from the micro-mosaic surface.…”
Section: Mass-transfer Studies With a Micro-mosaic Electrodementioning
confidence: 99%
See 4 more Smart Citations
“…Whitney and Tobias [143] used the MME to study the effect of single columns of electrolytically-generated gas bubbles on the mass transport to a vertically-oriented electrode. They found that a distinction could be made between bubbles generated on the MME itself, at a satellite segment, and bubbles evolved from a wire a some distance from the micro-mosaic surface.…”
Section: Mass-transfer Studies With a Micro-mosaic Electrodementioning
confidence: 99%
“…This is equivalent to a Reynolds number of 6700 [143]. Enhancement occurs because bubbles generated on an electrode rise inside of the diffusion boundary layer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations